AFP-producing adenocarcinoma of the esophagogastric junction: report of a case with atypical immunohistochemical findings responding to palliative chemotherapy with 5-fluorouracil, leucovorin, oxaliplatin, and docetaxel (FLOT regime) - Häussler, U.; Bitzer, M.; Bösmüller, H.; Clasen, S.; Götz, M.; Malek, N. P.; Plentz, R. R. (Zeitschrift für Gastroenterologie, 2016)
AFP-producing adenocarcinoma of the esophagus and esophagogastric junction are rare tumor diseases. These tumors show an aggressive behavior characterized by early occurrence of liver metastases and mimic hepatocellular carcinoma (HCC). A general recommendation for palliative therapy is not established for these special tumors.Here we report about a 61-year-old man with multiple liver metastases and high serum alpha-fetoprotein (AFP) level. First, HCC was suspected, but further evaluation showed an AFP-producing adenocarcinoma of the esophagogastric junction with unusual findings on further immunohistochemical analysis. Palliative chemotherapy with FLOT (5-fluorouracil, leucovorin, oxaliplatin, and docetaxel) regime showed a 9 month duration of partial response.
Keywords: Ösophaguskarzinom; Magenkarzinom; Barrett-Oesophagus